The effect of an antimony resistant bacterium on the iron plaque fraction and antimony uptake by rice seedlings. (March 2020) - Long, Jiumei; Zhou, Dongsheng; Li, Bingyu; Zhou, Yimin; Li, Yongjie; Lei, Ming
Abstract: Iron plaque (IP) is crucial in mitigating antimony (Sb) uptake and accumulation in rice plants, while, few studies focused on the effect of the iron plaque-associated Sb resistant bacteria on IP and Sb uptake into rice plants. Here, the effect of a Sb resistant bacterium (GenBank accession No. MH345840, with potential of conversion soluble Sb(III) into insoluble Sb2 O3 ) on IP and Sb(III)/Sb(V) uptake under hydroponic condition was investigated. The results showed that in the presence of Sb(III), a large quantity of bacterial cells consorted with IP on rice roots, the bacterial inoculum altered the IP fraction distribution without enhancing its amount. However, it reduced Sb(III) uptake into rice roots. On contrary, seldom bacterial cells associated with the IP on rice roots in the presence of the Sb(V), the bacterial inoculum increased the IP amount slightly, and did not decline the Sb(V) uptake into rice roots. It also showed that the bacterial inoculum decreased Sb concentrations in rice shoots greatly in both Sb(III) and Sb(V) supplied treatments. Graphical abstract: Image 1 Highlights: Iron plaque formation was promoted by the Fe 2+ supply. Bacterial inoculum promoted the sequestration of Sb(III) on iron plaque. Bacterial inoculum enhanced the carbonate-associated Fe in iron plaque. Bacterial inoculum increased the proportion of Sb(III) in rice roots. Bacterial inoculum decreased the Sb concentrations in rice shoots. Abstract : Main findings: The Sb resistant bacterium impacted the fraction and quantity of IP on rice roots, and it decreased the Sb concentrations in rice shoots.